HIV-Sheltering Platelets From Immunological Non-Responders Induce a Dysfunctional Glycolytic CD4+ T-Cell Profile - Zhu, Aiwei; Real, Fernando; Zhu, Jaja; Greffe, Ségolène; de Truchis, Pierre; Rouveix, Elisabeth; Bomsel, Morgane; Capron, Claude (Frontiers in Immunology, 2022)
Immunological non-responders (InRs) are HIV-infected individuals in whom the administration of combination antiretroviral therapy (cART), although successful in suppressing viral replication, cannot properly reconstitute patient circulating CD4+ T-cell number to immunocompetent levels. The causes for this immunological failure remain elusive, and no therapeutic strategy is available to restore a proper CD4+ T-cell immune response in these individuals. We have recently demonstrated that platelets harboring infectious HIV are a hallmark of InR, and we now report on a causal connection between HIV-containing platelets and T-cell dysfunctions. We show here that in vivo, platelet–T-cell conjugates are more frequent among CD4+ T cells in InRs displaying HIV-containing platelets (<350 CD4+ T cells/μl blood for >1 year) as compared with healthy donors or immunological responders (IRs; >350 CD4+ T cells/μl). This contact between platelet containing HIV and T cell in the conjugates is not infectious for CD4+ T cells, as coculture of platelets from InRs containing HIV with healthy donor CD4+ T cells fails to propagate infection to CD4+ T cells. In contrast, when macrophages are the target of platelets containing HIV from InRs, macrophages become infected. Differential transcriptomic analyses comparing InR and IR CD4+ T cells reveal an upregulation of genes involved in both aerobic and anaerobic glycolysis in CD4+ T cells from InR vs. IR individuals. Accordingly, InR platelets containing HIV induce a dysfunctional increase in glycolysis-mediated energy production in CD4+ T cells as compared with T cells cocultured with IR platelets devoid of virus. In contrast, macrophage metabolism is not affected by platelet contact. Altogether, this brief report demonstrates a direct causal link between presence of HIV in platelets and T-cell dysfunctions typical of InR, contributing to devise a platelet-targeted therapy for improving immune reconstitution in these individuals.